On Esteem-Based Incentives - Ali Mazyaki; Joël J. van der Weele (Tinbergen Institute, 2018)
Incentives based on esteem, honor and shame are increasingly popular and easy to use due to modern surveillance techniques. However, the use of shaming is controversial: critics argue that delegating punishment to a crowd can lead to mob justice and a loss of control over the size of the sanction. We use the signaling model of social behavior by Bénabou and Tirole (2011) to explore the effect of esteem-based incentives and their interaction with traditional monetary incentives. We show that esteem-based incentives can indeed lead to a loss of control by generating multiple equilibria, some of which feature high levels of stigma. Monetary and esteem incentives are interdependent. Moreover, if both types of incentives are costly to implement, the optimal incentive mix includes both instruments. In equilibrium, esteem-based incentives will be used relatively more for rare behaviors and in societies that have more heterogenous values.
Keywords: D02; H41; K42; 330; prosocial behavior; signaling; incentives; esteem